PENGARUH DISIPLIN KERJA DAN PELATIHAN TERHADAP KINERJA KARYAWAN DI PT BPR SEJAHTERA BATAM - Hartono, Tommy; Siagian, Mauli (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
Organization needs to manage their human resources well to have sustainability and advancement. To increase the performance of their employees, organizations need human resources with skills and abilities according to the vision and mission of the organization. This research aims to find out the impact of work discipline and training towards the performance of employees of PT BPR Sejahtera Batam, which consists of a total of 105 employees. This research uses saturated samples and the technique that the researcher is able to use is primary data by distributing questionnaire in the form of Google Forms. The data analysis method used are descriptive analysis, data quality test: validity test and reliability test, classic assumption test: normality test, multicollinearity and heteroscedasticity test, influence test: multiple regression analysis and coefficient determination test, and hypothesis test: T test and F test. The independent variables are work discipline (X1) and training (X2). Dominant impact towards dependent variables or performance of employees (Y) towards PT BPR Sejahtera Batam are Work Discipline Variable (X1) which has beta coefficient value of 0,728 or 72,8% which means that for every one point increment of work discipline variable (X1) is able to increase performance by 72,8% and for training variable (X2) with beta coefficient value of 0,335 or 33,5% which means that for every one point increment of training variable (X2) could increase performance by 33,5%. Work discipline bariable and training variable does influence performance, this can be see by the result of F test, which yield 131,371>f_table in the amount of 3,09.Keywords: discipline, employess performance, trainingÂ